Gallery walk as research method in information science - Rebecca Frank; Stephanie Krueger (Information Research: An International Electronic Journal, 2025)
Introduction. This paper argues that the gallery walks, a pedagogical technique traditionally used in educational settings, is an effective qualitative data collection strategy. Its interactive format stimulates discussion and ensures active participation, making it suitable for qualitative research.